The influence of board characteristics and state holding on corporate social responsibility disclosure, evidence from Vietnamese listed firms - Nguyen, Thi Lien Huong; Tran, Nhat Minh; Vu, Manh Chien (Business: Theory and Practice, 2021)
Analysing the nexus between board diversity, CEO power, state holding, and corporate social responsibility disclosure in an emerging country: Vietnam, where some listed firms are held significantly by the State, is the fundamental objective of this study. In order to achieve this goal, we employed regression analysis using panel data. While board diversity consists of board gender diversification and board independence and CEO (executive) power, consisting of executive duality, executive holding (ownership), and deputy CEO, and state ownership are explanatory variables, and CSR disclosure is a dependent variable. The sample contains of 166 Vietnamese listed firms at the Hanoi Stock Exchange (HNX) for 2014−2016. After performing regression analysis, the result revealed that the proportion of female directors, deputy CEO, and state holding had a significant correlation with CSR publication. In contrast, the proportion of independent directors, CEO duality, and CEO ownership was found to be insignificant. Our research adds to the research on firm governance and CSR in several approaches. First, the paper adds to the study on the advancement of research toward corporate social responsibility and firm governance and CEO features impress on it. Second, our research expands CSR literature in developing countries, which has not been treated in detail. Fourth, this research advances and adds literature to some theories, including agency theory and resource-based view theory.